Protein-Induced Pluripotent Stem Cells Ameliorate Cognitive Dysfunction and Reduce Aβ Deposition in a Mouse Model of Alzheimer's Disease. (15th August 2016) - Cha, Moon-Yong; Kwon, Yoo-Wook; Ahn, Hyo-Suk; Jeong, Hyobin; Lee, Yong Yook; Moon, Minho; Baik, Sung Hoon; Kim, Dong Kyu; Song, Hyundong; Yi, Eugene C.; Hwang, Daehee; Kim, Hyo-Soo; et al.
Abstract: Transplantation of stem cells into the brain attenuates functional deficits in the central nervous system via cell replacement, the release of specific neurotransmitters, and the production of neurotrophic factors. To identify patient-specific and safe stem cells for treating Alzheimer's disease (AD), we generated induced pluripotent stem cells (iPSCs) derived from mouse skin fibroblasts by treating protein extracts of embryonic stem cells. These reprogrammed cells were pluripotent but nontumorigenic. Here, we report that protein-iPSCs differentiated into glial cells and decreased plaque depositions in the 5XFAD transgenic AD mouse model. We also found that transplanted protein-iPSCs mitigated the cognitive dysfunction observed in these mice. Proteomic analysis revealed that oligodendrocyte-related genes were upregulated in brains injected with protein-iPSCs, providing new insights into the potential function of protein-iPSCs. Taken together, our data indicate that protein-iPSCs might be a promising therapeutic approach for AD.